Compensation for moral harm in violation of the right to disrespect for kinship and family ties - N. A. Temnikova; E. L. Nevzgodina (Правоприменение, 2024)
The admissibility of a wider application of compensation for moral harm in violation of family rights in the science of family law is assessed ambiguously. The law provides for such an opportunity only in art. 30 of the Family Code for a conscientious spouse when the marriage is declared invalid.It is necessary to take into account the specifics of family relations, as deeply personal, and the fact that art. 8 of the Family Code does not limit the protection of family rights in the ways specified in the legal norms, allowing the use of other methods. At the same time, in accordance with the provisions of art. 4 of the Family Code, the application of civil legislation to family relations is allowed, if it does not contradict the essence of family relations, which leads to refusals in a claim for compensation for moral harm due to the presence of obstacles to relatives from one of the parents in communicating with the child, due to the fact that the provisions of the current civil and family legislation do not provide for the possibility of his penalties.One of the most important reasons for the negative attitude of the courts to the fundamental permissibility of a wider application of the above-mentioned measure of responsibility in violation of family rights is seen in the absence of developed conditions for an offense that would be the basis for the application of compensation for moral harm, given that such conditions, taking into account the specifics of family relations, differ significantly from the usual conditions of civil liability.Goal. Identification of the criteria of private and family life applied by the European Court of Human Rights, as well as the study of the fundamental possibility of filing a claim for compensation for moral harm caused by the refusal of a parent to provide an opportunity to communicate with a child and participate in his upbringing to a separate parent.Methodology. In the course of the research, methods of generalization, description, analysis, synthesis, formal legal method were used.Results. The necessity of expanding the subject of proof in such a dispute with the inclusion of the following circumstances is justified. The presence of objective obstacles to communication, which can be associated with both the child (illness, unwillingness of the child to communicate with the parent), and with the personality of the parent living separately, communication with which can negatively affect the child. It is necessary to take into account the opinion and interests of the child. It is also necessary to take into account the actions of the parent himself, demanding compensation for moral harm, so if he evades the duties of maintaining his child, we assume the possibility of refusing the claim. Making a decision on compensation for moral harm involves taking into account the fault of the causer and his motives, which should not correspond to the interests of the child.